2002
DOI: 10.1079/phn2001259
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in nutrient intakes in the Melbourne Chinese Cohort Study

Abstract: Objective: To assess longitudinal changes in the consumption of nutrients and the impact of socio-economic factors on diet transition in the Melbourne Chinese Health Study (MCHS) cohort. Design: Longitudinal study including two phases: baseline (1989/90) and follow-up (1995/97). Settings: Melbourne metropolitan areas in Victoria, Australia. Study subjects and method: Two hundred and sixty-two Chinese men and women aged 25 years and over, recruited at baseline, who had completed the both baseline and follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 16 publications
1
11
1
Order By: Relevance
“…This study used a 7-day weighed food dairy and found no significant difference in energy intake. However, the findings contrast sharply with the Melbourne Chinese Cohort Study, composed of 262 Chinese adults with a mean age >50 years [42]. The authors found that intakes of energy, fats, fibre and protein increased significantly over eight years among women, but not men.…”
Section: Discussionmentioning
confidence: 61%
“…This study used a 7-day weighed food dairy and found no significant difference in energy intake. However, the findings contrast sharply with the Melbourne Chinese Cohort Study, composed of 262 Chinese adults with a mean age >50 years [42]. The authors found that intakes of energy, fats, fibre and protein increased significantly over eight years among women, but not men.…”
Section: Discussionmentioning
confidence: 61%
“…This study used a 7-day weighed food dairy and found no signi cant difference in energy intake. However, the ndings contrast sharply with the Melbourne Chinese Cohort Study, composed of 262 Chinese adults with a mean age >50 years [42]. The authors found that intakes of energy, fats, bre and protein increased signi cantly over eight years among women, but not men.…”
Section: Discussionmentioning
confidence: 69%
“…Migrants from non-English-speaking backgrounds (ie, Mediterranean, South Asian, South-East Asian, African or South Pacific Island) are more likely to develop diabetes or coronary heart disease 17 22 23 34. Unhealthy dietary habits coupled with reduced physical activity and a degree of isolation in social circles have greater negative consequences for female migrants, who are doubly marginalized as being a woman and a foreigner 16 18 24. These findings may explain our observations of a higher prevalence of GDM among the Australian Chinese migrants than the native Chinese, even after adjusting for age, BMI at booking and GA at booking.…”
Section: Discussionmentioning
confidence: 79%
“…The past few decades have shown a growth in research focusing on Chinese migrants’ health and acculturation in Western world, driven by the increasing number of Chinese migrants globally 8 10–12. Studies in Australia and other Western countries have shown that trends in lifestyle changed among Asians after migration, including increased consumption of take-away foods, decreased intake of fruits and vegetables, elevated degree of social strain and higher intake of red meats and dairy products 16 17 19 33 34. For example, in a review on Chinese migrants in Australia, researchers found substantial alteration or substitution of food items in their diet such as increased usage of fatty meat or cooking oil and soda consumption, instead of green leafy vegetable cooking and Chinese tea drinking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation